Screening of actinobacteria-producing amylolytic enzyme in sediment from Litopenaeus vannamei (Boone, 1931) ponds in Rembang District, Central Java, Indonesia (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Ayuningrum D, Sabdaningsih A, Jati OE. 2021. Screening of actinobacteria-producing amylolytic enzyme in sediment from Litopenaeus vannamei (Boone, 1931) ponds in Rembang District, Central Java, Indonesia. Biodiversitas 22: 1819-1828. Coastal environments are dynamic places where various activities such as aquaculture take place. Waste from intensive aquaculture contains high amounts of organic material that negatively affect the pond system as well as the surrounding environment. Bioremediation using hydrolytic enzymes from microbes has been widely used as an alternative to remove organic waste because of its lower economic cost and more efficient. Microbes such as Gram-positive actinobacteria are widely known as enzyme producers. This research aimed to isolate actinobacteria from Litopenaeus vannamei pond sediment, to purify and characterize the actinobacteria based on morphological appearance, to conduct screening of amylolytic activity, and to identify the species of actinobacteria through 16S rDNA amplification as well as to construct their phylogenetic tree. Sampling was done in Rembang District, Central Java, Indonesia, with 5 sampling stations consist of 14 sampling points. Thirty-eight pure axenic cultures of actinobacteria were successfully isolated using two different media, namely IM6 and IM8. The IM8 medium promoted the most growth of 24 isolates rather than on the IM6 with only 14 isolates. Based on morphological appearance, most isolates belonged to Streptomyces-like actinomycete bacteria as many as 30 isolates and the rest 8 isolates belonged to mycelium-forming non-Streptomyces actinomycete bacteria. The screening results of amylolytic activity showed that all of the 38 actinobacteria formed halo zone with amylolytic index between 1.31-5.29. Top five highest amylolytic index was found in isolates SA4.1 (IM6), SD1.3 (IM8), SC3.3 (IM8), SC3.3 (IM6) and SC3.2 (IM8). The isolate SC3.3 (IM8) according to BLAST homology, showed a 98% similarity with Streptomyces atacamensis C60. Further research is needed to investigate the potential of isolate SC3.3 (IM8) to reduce the BOD level in the aquatic system as a bioremediator candidate.
Keywords: Bioremediation, hydrolytic enzyme, organic waste, mycelium-forming non-Streptomyces actinomycete, Streptomyces-like actinomycete